Implementing COOL: comparative welfare effects of different labeling schemes - Joseph, Siny; Lavoie, Nathalie; Caswell, Julie A. (My University, 2014)
Country-of-origin labeling (COOL) is being implemented in different forms and degrees in the United States and other countries across the world. The first implementation of mandatory country of origin labeling (MCOOL) in the United States was for seafood in 2005. This is an example of partial MCOOL because it exempts the foodservice sector and excludes processed seafood from labeling. Using a conceptual framework, we analyze the welfare impacts of partial MCOOL when compared to no, voluntary, and total mandatory COOL, taking into account imperfect competition in the downstream markets, information asymmetry, and diversion of low-quality product to the unlabeled market. The model is general enough to apply to any incomplete regulation for which the perceived low-quality product is required to be labeled, such as the labeling of genetically modified food in the European Union. Our results show that when consumers have a strong enough preference for domestic relative to imported product, regulators can overestimate the gain in consumer welfare from partial mandatory labeling if they ignore the diversion of lower quality imports to the unlabeled sector. We show that if the preference for domestic product is large enough, total MCOOL benefits the home market the most overall, including domestic consumers and producers, but not the imperfectly competitive downstream agents. However, if total MCOOL is too costly to implement, partial MCOOL is the second-best solution, but only if consumers falsely believe the unlabeled product to be of higher quality than it truly is. Our results suggest more research is needed to determine the extent to which consumers value the information provided by MCOOL and to enable regulators to consider the welfare impact of diversion in evaluating incomplete mandatory labeling regulations.
Keywords: Country of origin labeling; Product differentiation; Information asymmetry; Food quality; Incomplete regulation